Supplementing essential amino acids with the nitric oxide precursor, l-arginine, enhances skeletal muscle perfusion without impacting anabolism in older men - Mitchell, W. Kyle; Phillips, Bethan E.; Wilkinson, Daniel J.; Williams, John P.; Rankin, Debbie; Lund, Jonathan N.; Smith, Kenneth; Atherton, Philip J. (Elsevier, 2017)
Postprandial limb blood flow and skeletal muscle microvascular perfusion reduce with aging. Here we tested the impact of providing bolus essential amino acids (EAA) in the presence and absence of the nitric oxide precursor, l-Arginine (ARG), upon skeletal muscle blood flow and anabolism in older men. Healthy young (YOUNG: 19.7 ± 0.5 y, N = 8) and older men (OLD, 70 ± 0.8 y, N = 8) received 15 g EAA or (older only) 15 g EAA +3 g ARG (OLD-ARG, 69.2 ± 1.2 y, N = 8). We quantified responses in muscle protein synthesis (MPS; incorporation of 13C phenylalanine into myofibrillar proteins), leg and muscle microvascular blood flow (Doppler/contrast enhanced ultrasound (CEUS)) and insulin/EAA in response to EEA ± ARG. Plasma EAA increased similarly across groups but argininemia was evident solely in OLD-ARG (∼320 mmol, 65 min post feed); increases in plasma insulin (to ∼13 IU ml−1) were similar across groups. Increases in femoral flow were evident in YOUNG >2 h after feeding; these effects were blunted in OLD and OLD-ARG. Increases in microvascular blood volume (MBV) occurred only in YOUNG and these effects were isolated to the early postprandial phase (+45% at ∼45 min after feeding) coinciding with detectable arterio-venous differences in EAA reflecting net uptake by muscle. Increases in microvascular flow velocity (MFV) and tissue perfusion (MBV × MFV) occurred (∼2 h) in YOUNG and OLD-ARG, but not OLD. Postprandial protein accretion was greater in YOUNG than OLD or OLD-ARG; the latter two groups being indistinguishable. Therefore, ARG rescues aspects of muscle perfusion in OLD without impacting anabolic blunting, perhaps due to the “rescue” being beyond the period of active EAA-uptake.